City watch : discovering the uncommon Chicago - Anderson, Jon, 1936-2014 (University of Iowa Press, 2001)
In forty-five years as one of Chicago's liveliest journalists for Time, Life, and the Chicago Tribune, Jon Anderson has established a reputation for picking up on what someone once called "the beauty of the specific fact." Part "Talk of the Town," part On the Road with Charles Kuralt, Anderson's twice-a-week "City Watch" columns in the Chicago Tribune seek out interesting and unexpected people and places from the everyday life of what the author calls the "most typical American big city." In the process he discovers the joys and triumphs of ordinary people.